Effect of binder mineral in batchery waste based feed pellet on its proximate component and energy values - Sulistiyanto, B.; Utama, C.S.; Sumarsih, S. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The Experiment was conducted to study effects of binder mineral addition to the hatchery waste based pelletprocessingon its proximate component and energy value. The study may be beneficial to emerge a new feed resource for local farm businesses. The hatchery wastes those comprised of 30% of egg shells, 60% of un-hatched eggs, and 10% of culled DOC were blended, and mixed with 10% of cassava cake meal(W/W), then mixed well with mineral adsorbent (bentonites or zeolites) at 0, 1, 2, 3, 4 and 5% (W/W). The mixture was conditioned at 80 ºC for 15 min, and extruded to make a pellet with 6 mm of diameter and 30 mm in length, and dried into warm air flow dryer. The moisture, crude protein (CP), ash, ether extract (EE), crude fiber (CF), apparent metabolizable energy (AME), true metabolizable energy (TME), metabolizability(MET) and nitrogen retention (NR) were observed in each pellet. Result of the experiment showed that moisture of pellet was decreased (P<0.05) by zeolites or bentonites addition. Even though the effect ofbinder mineral addition gave different patterns, concentrations of ash, crude protein, ether extract and crude fiber of pellet product were increased by increasing level of mineral adsorbent (P<0.05). Nutrient availability as was represented by AME, TME, MET, and NR were increased by zeolites and bentonites additions (P<0.05). In conclusion, supplementations of bentonites and zeolites in the hatchery waste based pelletcould improve its proximate component concentration and nutrient availability.